Efektivitas Website Polres Solok Kota Sebagai Pelayanan Informasi Publik ditinjau dari Parameter Kehumasan - Putra, Nofri Andeska; Darwis, Yuliandre (CV. ITTC INDONESIA, 2024)
This research aims to determine the effectiveness of the Solok City Police website as a public information service. This research uses qualitative research methods, with data collection techniques through observation, interviews, and document studies. The data analysis used are data reduction, data presentation, data verification and drawing conclusions. The website is evaluated based on four public relations parameters, namely strategic counsel, media relations, community relations, and government relations. The results showed that the Solok City Police website has not been effective in supporting public information service functions including information related to police programs and services, internal regulations and policies, and no routine criminal statistics data. Interactive website features also do not function so that the implementation of community relations is not effective in involving public participation. Content related to advocating Police needs to the government and the Regional House of Representatives is still lacking. The Solok City Police website needs to increase its capacity to be more optimal in its implementation and only fulfills a small portion of its capacity and function as an effective public information media. Improvements and updates to the website are needed in terms of content and interface display so that they are always relevant to support the implementation of Police tasks and public information needs.